2019
DOI: 10.1177/1369433219872440
|View full text |Cite
|
Sign up to set email alerts
|

An efficient discrete optimization algorithm for performance-based design optimization of steel frames

Abstract: Performance-based design optimization of steel frames, with element sections selected from standard sections, is a computationally intensive task. In this article, an efficient discrete optimization algorithm is proposed for performance-based design optimization of steel frames. The computational efficiency is improved by searching in a sensible manner, guided by the deformation information of structural elements. To include all standard sections in the design space, the cross-sectional area ( Area) and moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…According to a previous research (Wang et al, 2020), standard sections can be uniquely determined by their Area and I . Thus, to continuously define the cross-sectional properties of structural elements, in this study a convex combination of standard sections is proposed:…”
Section: Semidefinite Programming-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous research (Wang et al, 2020), standard sections can be uniquely determined by their Area and I . Thus, to continuously define the cross-sectional properties of structural elements, in this study a convex combination of standard sections is proposed:…”
Section: Semidefinite Programming-based Approachmentioning
confidence: 99%
“…As the interpolation schemes almost always involve high-degree polynomials, only nonlinear programming can be formulated and therefore the solutions are at most local optimum. Also, according to a previous study by the authors (Wang et al, 2020), the use of interpolation schemes is problematic in that many standard sections cannot be covered by the interpolation schemes, thus many sections have to be ruled out of the continuous design space.…”
Section: Introductionmentioning
confidence: 99%
“…Pipe racks are considered as industrial non-building structures (ASCE, 2010) which support pipes and other relevant mechanical or electrical equipment in petrochemical and power plants. Only some studies exist on design concepts and/or design optimization of pipe rack structures (Arya et al, 2003; Bedair, 2015; Bhattacharya et al, 2008; di Roseto et al, 2017; Di Sarno and Karagiannakis, 2019; Lee et al, 2015; Villaverde, 1997), while there are many works on optimal design of building frames (Dogan and Ozyuksel Ciftcioglu, 2020; Doğan and Saka, 2012; Gholizadeh, 2015; Gholizadeh and Moghadas, 2014; Kaveh and Bakhshpoori, 2013; Saka, 2009; Wang et al, 2020; Zakian, 2019) and trusses (Kaveh and Bakhshpoori, 2016; Kaveh and Zakian, 2014a, 2018), among which a part of them are briefly discussed herein. Arya et al (2003) compared a manually designed pipe rack with an automated design using STRUDL-II software in three different cases of imposing design constraints and concluded that the software design can reduce the structural weight while thoroughly following the requirements of standards.…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos, foram realizados diversos trabalhos relacionados a otimização estrutural. Entre eles, pode-se citar: Truong e Kim [25]; Kaveh e Ghazaan [26]; Kaveh, Kabir e Bohlool [27]; Tu, He e Huang [28]; Wang et al [29]; Alkhadashi et al [30]; Do e Ohsaki [31]; Ghasemof, Mirtaheri e Mohammadi [32]; Gholizadeh e Fattahi [33] e Shen, Ohsaki e Yamakawa [34]. No Quadro 1 é apresentado um resumo com os trabalhos mais relevantes citados na presente revisão bibliográfica, além dos trabalhos relacionados publicados nos últimos cinco anos, destacando as funções-objetivo, restrições e variáveis de projeto aplicadas em cada um, que são representadas por: peso da estrutura (W), deslocamentos (D), tensões e esforços internos (T), frequências naturais de vibração (F), estabilidade global e confiabilidade estrutural (E), seções transversais (S), orientações dos pilares (O) e posições de apoios (P).…”
Section: Revisão Da Literaturaunclassified
“…Apesar de existirem estudos considerando posições de apoios e orientações das seções transversais de pilares como variáveis de projeto, não são encontrados trabalhos de otimização multi-objetivo de pórticos espaciais em aço que consideram estas duas simultaneamente nem que consideram funções-objetivo relacionadas à estabilidade global e ao comportamento dinâmico. ✓ ✓ Raich e Ghaboussi [22] ✓ ✓ ✓ ✓ ✓ Rong, Xie e Yang [12] ✓ ✓ ✓ ✓ Kızılkan [17] ✓ ✓ ✓ ✓ ✓ Lemonge e Barbosa [18] ✓ ✓ ✓ ✓ Toğan [14] ✓ ✓ ✓ ✓ ✓ ✓ Petprakob [23] ✓ ✓ ✓ Barraza et al [35] ✓ ✓ ✓ ✓ Gholizadeh e Baghchevan [15] ✓ ✓ ✓ ✓ ✓ Oliveira [24] ✓ ✓ ✓ ✓ ✓ ✓ ✓ Truong e Kim [25] ✓ ✓ ✓ ✓ ✓ Zakian [11] ✓ ✓ ✓ Kaveh e Ghazaan [26] ✓ ✓ ✓ ✓ Kaveh, Kabir e Bohlool [27] ✓ ✓ ✓ ✓ Resende et al [16] ✓ ✓ ✓ ✓ ✓ ✓ ✓ ✓ ✓ Tu, He e Huang [28] ✓ ✓ ✓ ✓ ✓ Wang et al [29] ✓ ✓ ✓ ✓ Alkhadashi et al [30] ✓ ✓ ✓ ✓ Do e Ohsaki [31] ✓ ✓ ✓ ✓ ✓ Ghasemof, Mirtaheri e Mohammadi [32] ✓ ✓ ✓ ✓ ✓ Gholizadeh e Fattahi [33] ✓ ✓ ✓ Motta et al [19] ✓ ✓ ✓ ✓ ✓ ✓ ✓ ✓ Shen, Ohsaki e Yamakawa [34] ✓ ✓ ✓ ✓…”
Section: Revisão Da Literaturaunclassified